2007
DOI: 10.1016/j.jcrs.2007.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Causes of intraocular lens opacification or discoloration

Abstract: Various pathologic processes may lead to clinically significant opacification or discoloration of the optic component of intraocular lenses (IOLs) manufactured from different biomaterials and in different designs. Factors such as the patient's associated conditions, the manufacturing process, the method of IOL storage, the surgical technique and adjuvants, or a combination of these may be involved. The complication may be observed intraoperatively or postoperatively from a few hours after implantation to many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
101
1
18

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(128 citation statements)
references
References 49 publications
2
101
1
18
Order By: Relevance
“…2 Postoperative calcification represents the most important indication for explantation of hydrophilic acrylic IOLs. [2][3][4][5][6][7] Silicone lenses were also shown to calcify in eyes with asteroid hyalosis. [8][9][10] The condition named snowflake degeneration of rigid polymethylmethacrylate (PMMA) lenses still leads to explantation of a significant number of these IOLs, although it is usually observed in three-piece lenses manufactured in the 80s and early 90s.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Postoperative calcification represents the most important indication for explantation of hydrophilic acrylic IOLs. [2][3][4][5][6][7] Silicone lenses were also shown to calcify in eyes with asteroid hyalosis. [8][9][10] The condition named snowflake degeneration of rigid polymethylmethacrylate (PMMA) lenses still leads to explantation of a significant number of these IOLs, although it is usually observed in three-piece lenses manufactured in the 80s and early 90s.…”
mentioning
confidence: 99%
“…11,12 Calcification and snowflake degeneration are leading causes of clinically significant IOL opacification. 3 Clinical studies on opacified IOLs demonstrated that they may be more associated with complaints of glare and ''foggy'' or ''cloudy'' vision, while visual acuity is not drastically reduced. 13,14 The quality of vision loss in affected patients appears to be predominantly related to increased forward light scattering and subsequently retinal stray light, which can give rise to a variety of subjective complaints, including glare in various illuminating conditions, halos around bright lights, color and contrast loss, as well as hazy vision.…”
mentioning
confidence: 99%
“…Factors such as the patient's associated conditions, the manufacturing process, the method of IOL storage, the surgical technique and adjuvants, or a combination of these may be involved. Hydrophobic materials are specially opacified by excess influx of water, while hydrophilic IOLs are mostly affected by the formation of deposits/precipitates on the IOL surface or within the IOL substance 11,12,13 . Furthermore, direct discoloration by capsular dyes or medications, coating by substances such as ophthalmic ointment and silicone oil, and a slow, progressive degradation of the IOL biomaterial may be involved in the different designs of IOL opacification process.…”
Section: B Discussionmentioning
confidence: 99%
“…11,17 Papers evaluating medical illness in association with IOL opacification suggest that a mechanism of bloodaqueous barrier impairment seemed to be associated with this postsurgical complication. 18 According to the literature, hydrophilic acrylic IOLs are likely to develop calcification when the concentrations of calcium, phosphate and albumin in the aqueous humor fluctuate due to blood-aqueousbarrier breakdown or other factors.…”
Section: B Discussionmentioning
confidence: 99%
“…Problemas como deteriorização, opacificação e descoloração dos materiais das lentes têm sido relatados (1)(2)(3)(4)(5)(6)(7)(8) . Qualquer que seja a origem do comprometimento da lente intraocular, como manifestação clínica comum, ocorre perda progressiva da acuidade visual que pode resultar na extração e substituição por um novo implante intraocular.…”
Section: Introductionunclassified